Prognosis of breast cancer during pregnancy: evidence for nursing care - Fernandes, Ana Fátima Carvalho (2011)
This integrative review analyzed evidence available in the literature concerning the prognosis of breast cancer during pregnancy. The following databases were used for selecting studies: PubMed, CINAHL and LILACS. A total of 240 primary studies were identified; 13 papers were included in the integrative reviews sample after reading the titles and abstracts and according to the established inclusion and exclusion criteria. There is evidence indicating that pregnancy does not worsen the evolution of breast cancer and a poor prognosis is related to late stage tumors. Among the gaps identified in the studied theme, the need for further studies addressing nursing care provided to pregnant women with breast cancer is highlighted in order to promote improved care in the context of health care.